Simulation of saturation current in In1-xGaxSb based solar cell - Hassan, Asif S.; Mondol, Raktim Kumar; Jafar, Imran Bin (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 3rd International Conference on Green Energy and Technology, ICGET 2015; University of Dhaka Dhaka; Bangladesh; 11 September 2015 through 12 September 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICGET.2015.7315122